Prolonged moderate to vigorous physical activity may lead to a decline in cognitive performance: a Mendelian randomization study - Li, Yutao; Fu, Chenyi; Song, Honglin; Zhang, Zhenhang; Liu, Tianbiao (Frontiers in Aging Neuroscience, 2024)
Objective: This study investigates the causal relationship between moderate to vigorous physical activity and cognitive performance. Methods: Genetic loci strongly related to moderate to vigorous physical activity from genome-wide association studies were used as instrumental variables. These were combined with genetic data on cognitive performance from different Genome-Wide Association Study (GWAS) to conduct a two-sample Mendelian randomization analysis. The primary analysis used inverse variance weighting within a random effects model, supplemented by weighted median estimation, MR-Egger regression and other methods, with results expressed as Beta coefficient.Results: This study selected 19 SNPs closely related to physical activity as instrumental variables. The multiplicative random-effects Inverse-Variance Weighted (IVW) analysis revealed that moderate to vigorous physical activity was negatively associated with cognitive performance (Beta = -0.551; OR = 0.58; 95% CI: 0.46-0.72; P < 0.001). Consistent results were obtained using the fixed effects IVW model (Beta = -0.551; OR = 0.58; 95% CI: 0.52-0.63; P < 0.001), weighted median (Beta = -0.424; OR = 0.65; 95% CI: 0.55-0.78; P < 0.001), simple mode (Beta = -0.467; OR = 0.63; 95% CI: 0.44-0.90; P < 0.001), and weighted mode (Beta = -0.504; OR = 0.60; 95% CI: 0.44-0.83; P < 0.001). After adjusting for BMI, smoking, sleep duration, and alcohol intake frequency, the multivariate MR analysis also showed a significant association between genetically predicted MVPA and cognitive performance, with Beta of -0.599 and OR = 0.55 (95% CI: 0.44-0.69; P < 0.001).The findings of this study indicate that genetically predicted moderate to vigorous physical activity may be associated with a decline in cognitive performance.